Royal Australian and New Zealand College of Psychiatrists clinical practice guideline for the management of deliberate self-harm. (October 2016) - Carter, Gregory; Page, Andrew; Large, Matthew; Hetrick, Sarah; Milner, Allison Joy; Bendit, Nick; Walton, Carla; Draper, Brian; Hazell, Philip; Fortune, Sarah; Burns, Jane; Patton, George; et al.
Objective: To provide guidance for the organisation and delivery of clinical services and the clinical management of patients who deliberately self-harm, based on scientific evidence supplemented by expert clinical consensus and expressed as recommendations. Method: Articles and information were sourced from search engines including PubMed, EMBASE, MEDLINE and PsycINFO for several systematic reviews, which were supplemented by literature known to the deliberate self-harm working group, and from published systematic reviews and guidelines for deliberate self-harm. Information was reviewed by members of the deliberate self-harm working group, and findings were then formulated into consensus-based recommendations and clinical guidance. The guidelines were subjected to successive consultation and external review involving expert and clinical advisors, the public, key stakeholders, professional bodies and specialist groups with interest and expertise in deliberate self-harm. Results: The Royal Australian and New Zealand College of Psychiatrists clinical practice guidelines for deliberate self-harm provide up-to-date guidance and advice regarding the management of deliberate self-harm patients, which is informed by evidence and clinical experience. The clinical practice guidelines for deliberate self-harm is intended for clinical use and service development by psychiatrists, psychologists, physicians and others with an interest in mental health care. Conclusion: The clinical practice guidelines for deliberate self-harm address self-harm within specific population sub-groups and provide up-to-date recommendations and guidance within an evidence-based framework, supplemented by expert clinical consensus.